EDUCATION ON THE INTRODUCTION OF SPEOS AND AROMATHERAPY METHODS AS AN EFFORT TO INCREASE BREAST MILK PRODUCTION IN BREASTFEEDING MOTHERS IN DENPASAR CITY - Widiantari, WD (Jurnal Abdi Mahosada, 2025)
Breast milk is the best food a baby needs in the first 6 months of life. Prolactin hormone plays a role in the process of milk formation and oxytocin hormone plays a role in the process of milk ejection. How the oxytocin hormone works is affected by psychology, stress, excessive worry and unhappiness. The Stimulation of Endorphin and Oxytocin Massage (SPEOS) method is a combination of endorphin, oxytocin, and suggestive massage stimulation performed sequentially. The role of the pituitary is to release endorphins from the body, the effect resembles heroin and morphine, besides giving aromatherapy also greatly helps the production of breast milk because it is very calming. The purpose of this PKM is to increase the knowledge of breastfeeding mothers and increase the role of husbands as a support system in breastfeeding. The preparation stage is carried out during the assessment and approach. The implementation stage is carried out by providing information about the benefits of breastfeeding for child development, introduction to the SPEOS method and aromatherapy. The PKM results obtained an increase in maternal knowledge before and after being given education related to the SPEOS and aromatherapy methods, the material provided is the definition of SPEOS and Aromatherapy, the benefits of SPEOS and Aromatherapy, SPEOS techniques and the use of aromatherapy. Conclusion: It is hoped that mothers can provide optimal breast milk to their babies by applying the SPEOS method and assisted by their husbands and family members.